Safety of Dupilumab Therapy for Atopic Dermatitis during Pregnancy: A Systematic Review and Meta-analysis - Verónica Sánchez-García; Eva de-Miguel-Balsa; José-Manuel Ramos-Rincón; Isabel Belinchón-Romero (Acta Dermato-Venereologica)
Atopic dermatitis (AD) is the most common skin condition among pregnant women. However, there is limited information on the safety of biologicals during pregnancy. A systematic review and meta-analysis was conducted following the PRISMA guidelines to evaluate the effects of exposure to biologicals during pregnancy and/or preconception in women with AD, and to estimate the pooled prevalence of spontaneous abortions and congenital malformations in their newborns. MEDLINE, Embase, Scopus, and Web of Science to 31 May 2024 were searched to identify randomized controlled trials and non-randomized studies. To test the robustness of our findings, sensitivity analyses were performed. Fifteen observational studies involving 115 pregnant women with a mean age of 33.46 years (standard deviation [SD] 3.02 were included). All studies evaluated dupilumab. The mean duration of exposure to dupilumab during pregnancy was 27.52 weeks (SD 11.16). The weighted prevalence of spontaneous abortions was 18.9% (95% confidence interval 5.3 to 38.2). There were no reports of congenital malformations. The sensitivity analyses showed no significant differences in weighted prevalences. In conclusion, the current scientific evidence suggests that dupilumab is probably safe during pregnancy and preconception in women with AD, with no significant increase in the risk of miscarriage or congenital malformations compared to the general population. However, the results of this review are inconclusive due to the limited number of large, well-designed clinical studies.